1976
DOI: 10.1007/bf00041524
|View full text |Cite
|
Sign up to set email alerts
|

Mutation breeding of Chrysanthemum morifolium Ram. using in vivo and in vitro adventitious bud techniques

Abstract: Chrysanthemum morifolium, explants, mutation breeding, adventitious bud technique, chimeral and nonchimeral mutants, in vivo, in vitro, X-rays, solid mutants. SUMMARYDuring experiments, which are being carried out to study the factors which control the process of adventitious bud formation in vivo on detached leaves of Chrysanthemum morifolium RAM, adventitious shoots were produced from leaves, irradiated with 500 rad of X-rays. The most important but disadvantageous result was that the majority of the adventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 9 publications
0
26
1
Order By: Relevance
“…Furthermore, mutation induction often results in chromosomal aberration and consequently obtains mutants with both desirable and undesirable traits. In periclinal chimaeras solely possessing a mutated LI-layer, 'negative' alterations of flower size, plant height, yield etc., are not always expressed (Broertjes et al, 1976).…”
Section: Flower Colour Chimaerasmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, mutation induction often results in chromosomal aberration and consequently obtains mutants with both desirable and undesirable traits. In periclinal chimaeras solely possessing a mutated LI-layer, 'negative' alterations of flower size, plant height, yield etc., are not always expressed (Broertjes et al, 1976).…”
Section: Flower Colour Chimaerasmentioning
confidence: 97%
“…Broertjes et al (1976) showed, that plants regenerated via adventitious buds from irradiated in vivo leaves of chrysanthemum cv. Bravo were chimaeras in the majority of cases.…”
Section: Flower Colour Chimaerasmentioning
confidence: 98%
“…These variations, which are more or less frequent depending on the cultivar, seem to be related to the fact that many cultivars of chrysanthemum are periclinal chimeras, with one cell layer genetically different to the others (Dowrick andEl-Bayoumi 1965, Martín et al 2002). In the last few years, modern breeding techniques have been incorporated to obtain new cultivars: radiation-induced mutation (Broertjes et al 1976), somaclonal variation induction (Malaure et al1991, Rout andDas 1997) and, more recently, genetic transformation (see review of Teixeira da Silva 2003).…”
Section: Introductionmentioning
confidence: 99%
“…With mutation breeding for quantitative characters chimera formation is a great problem. BROERTJES et al (1976) showed that in vitro regeneration of adventitious buds from pedicel explants solved that problem.…”
Section: Introductionmentioning
confidence: 99%